PROBLEMS IN TRANSLATING ENGLISH PHRASEOLOGISMS INTO UZBEK - Jumayeva Sadbarg Mirolimovna (Bright Mind Publishing, 2025)
One of the most challenging and fascinating problems in the field of contemporary translation theory is phraseological translation. This article explains the challenges that arise when translating phraseological units from English and identifies the key elements that need to be taken into account.
Keywords: Translation talent, figurative-stylistic meaning, phraseological picture, phraseology, and phraseological units.